2013
DOI: 10.5664/jcsm.2498
|View full text |Cite
|
Sign up to set email alerts
|

Narcolepsy-Cataplexy: Is Streptococcal Infection a Trigger?

Abstract: Narcolepsy-cataplexy is an uncommon sleep disorder which may present in childhood. We report a case of an 8-year-old presenting with narcolepsy-cataplexy following a streptococcal infection. Autoimmune etiology for narcolepsy has been suggested. In our patient increased anti-streptolysin O and antiDNAse B titers were noted. As suggested by recent cases, the streptococcal infection was likely a trigger for narcolepsy onset in this genetically predisposed child. The patient was initially diagnosed as having Syde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…This mechanism is supported by the strong association of HLA DQB1*0602 phenotypes with the development of narcolepsy 9 . Numerous articles have reported the development of narcolepsy in patients with the HLA DQB1*0602 phenotype following infections, especially streptococcal infections and flu 11,12,[19][20][21] . Of note, an increase in the incidence of narcolepsy was reported during the 2009 H1N1 influenza pandemic and after massive flu vaccination in some countries 12,[22][23][24] , especially among people younger than 18 years and in France, Denmark, Finland, and Sweden 22 .…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism is supported by the strong association of HLA DQB1*0602 phenotypes with the development of narcolepsy 9 . Numerous articles have reported the development of narcolepsy in patients with the HLA DQB1*0602 phenotype following infections, especially streptococcal infections and flu 11,12,[19][20][21] . Of note, an increase in the incidence of narcolepsy was reported during the 2009 H1N1 influenza pandemic and after massive flu vaccination in some countries 12,[22][23][24] , especially among people younger than 18 years and in France, Denmark, Finland, and Sweden 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the patient showed increase in the ASLO values when diagnosed with this affection. ASLO is an indication of a previous contact (during the past 2 months) with S. pyogenes (beta-hemolytic streptococcus of the A group) [20] .…”
Section: Discussionmentioning
confidence: 99%
“…17 Population studies have shown that the risk of narcolepsy is increased 5.4-fold (95% confidence interval = 1.5-19.1) in subjects with a history of a physician-diagnosed streptococcal pharyngitis. 14,15 Streptococcal infections can stimulate autoimmunity by cross-linking T cell receptor molecules and major histocompatibility complex molecules independently of antigen presentation. 15 In a study from China, Han et al monitored the incidence of narcolepsy and found out that the occurrence of childhood narcolepsy cases was found to increase 3-fold following the winter of 2009-2010, suggesting that H1N1 infections may increase susceptibility to narcolepsy in children.…”
Section: Discussionmentioning
confidence: 99%